Sirtuin Genes and Functions - Bayram, Ali; İğci, Mehri (Fırat University, 2013)
Many studies have been conducted on the potential role, on several diseases, of 23 Sirtuin (SIRT) family genes known as NAD + dependent class III deacetylase enzymes. Regarding the published literature, Sirtuins have been thought to play a significant role on the treatment of diabetes type II, obesity, cancer, aging, and several neuro-degenerative diseases. As a result of recent studies, in order to be able to study the role of SIRT genes on biological systems, which is providing positive results for the treatment of many diseases, it is important to understand the molecular and chemical structure of them.

NAD + bağımlı sınıf III deasetilaz enzimler olarak bilinen Sirtuin (SIRT) ailesi genleri ile ilgili olarak çeşitli hastalıklardaki potansiyel rolü üzerine birçok çalışma yapılmıştır. Yayımlanmış literatüre dayanarak Sirtuinlerin; tip II diyabet, obezite, kanser, yaşlanma ve çeşitli nörodejeneratif hastalıkların tedavisinde önemli rol oynadığı düşünülmektedir. Son yapılan çalışmalar sonucu birçok sağlık probleminin tedavisine yönelik olumlu sonuçlar veren SIRT genlerinin biyolojik sistemlerdeki rolünü çalışabilmek için moleküler ve kimyasal yapısını anlamak çok önemlidir.
Sirtuin Genleri ve İşlevleri